CLIMATE VILLAGE: PRODUCTION OF CITIZEN’S KNOWLEDGE AND SOCIAL SPACE ON CLIMATE CHANCE ISSUE - Siti Zunariyah (Riviera Publishing, 2024)
The climate change issue is authentic and recognized as the biggest threat to human life. Many actions should be taken to adapt to and mitigate climate change, one of which is to hold a Climate Village Program. This research aimed to describe the public participation process in developing Climate Village and the factors affecting it. The research was conducted in the Sekip Climate Village of Kadipiro of Surakarta City using ethnographic methods with Henry Lefebvre's social space reproduction. The urgency of Climate Village development in Sekip village is the environmental problem that has been faced since 2011, including flood, water puddles, drought, DBF, malaria epidemic, slump, and dirty village image. Production of knowledge and social space to develop climate villages was conducted through adaptation and mitigation activities. The program of adapting to climate change is the natural form of community action taken by constructing infiltration wells, repairing gutters, constructing retention basins, planting vegetables and fruits, and installing vertical gardens. The mitigation program included waste management, solar panel installation, bio-pore hole construction, and rainwater harvesting activities. The production of citizens' spatial space was conducted based on citizens' knowledge production concerning the effect of climate change and knowledge reproduction about adaptation and mitigation that can be accomplished in a participative manner. The factors affecting it, including ecology and social culture, became part of citizens' social learning process to mitigate the effect of climate change.